If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+2)=2(3-x)
We simplify the equation to the form, which is simple to understand
5(x+2)=2(3-x)
Reorder the terms in parentheses
+(+5x+10)=2*(3-x)
Remove unnecessary parentheses
+5x+10=+2+*(+3-x+)
Reorder the terms in parentheses
+5x+10=+(+6-2x)
Remove unnecessary parentheses
+5x+10=+6-2x
We move all terms containing x to the left and all other terms to the right.
+5x+2x=+6-10
We simplify left and right side of the equation.
+7x=-4
We divide both sides of the equation by 7 to get x.
x=-0.571428571429
| 7x=12+2x | | 0=-7t-21 | | 2X-3Y=31 | | -c+-7+8c+-3=4 | | 4/5u=1/4 | | 4/3X-5 | | 14.96+0.13x=0.39x-15 | | 0.39x-15=50 | | -7/6y=8 | | W+3/2=5/2 | | 2(d+8)-5d=6 | | (x)=4x-6 | | 5x=15+x | | 9.4y-8.4y+9.2=-9.8-8.8 | | (-3x+15)+(8x-43)= | | -7k+-4k=40-53 | | 4(6+N)=30 | | 5-m=5-6m | | 72+-80=-1(4n+-8) | | X^2-20x+96= | | 3w-12=-6w+15 | | r/-5*-5 | | -1(-2x+4)=-96 | | x+4/3=x-4/7 | | 5/8c-8=15 | | -u+6=-3u | | -20+6=-8w-2w | | 194-4x=41x+24 | | 274-4x=41x+19 | | -70=2(g-3) | | 2n+-8=37 | | 5x-68=3-10 |